The addition of cashew pseudo-fruit by different concentration towards chemical and organoleptic quality of dumbo catfish floss - Ardiansah, Bayu; Marianah, Marianah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
Shredded floss is a food product made from main raw materials, namely beef, chicken and fish. Shredded floss is generally used as an energy source because it contains a lot of protein. This study aims to determine the effect of the addition of cashew fruit on the chemical and organeleptic properties of African catfish shredded. This study was designed using a Completely Randomized Design (CRD). Data were analyzed using the Honest Significant Difference Test (BNJ) at 5% level in one aspect, namely the addition of cashew and African catfish pseudo-fruits with the following treatments: P0 0%: (100% African catfish meat as control), P1 African catfish meat mixture 100%: 20% cashew fruit, according to the weight of the ingredients, P2 A mixture of African catfish meat 100%: 30% cashew pseudo fruit, 100% P3 A mixture of African catfish meat: 40% cashew pseudo fruit, P4 African catfish 100% cashew fruit 50%. The results of this study indicate that the treatment of adding cashew fruit to the chemical and organeleptic properties of shredded catfish has an effect on significantly on chemical properties (parameters moisture content, protein content and fiber content) whereas organeleptic properties have a significant effect on parameters of color, taste and aroma, but no significant effect on texture. The best treatment was obtained in the P3 treatment (200 grams of African catfish meat 40% cashew nuts) with a water content of 14.62%, protein content of 17.10%, fiber content of 32.49%. The taste is very like, the color is slightly brownish, the aroma is like and the texture is rough.